Child Rights Protection in Fasakh Cases Due to Apostasy: A Juridical Analysis of the Decision of the Cibadak Religious Court Number 3112/Pdt.G/2024/PA.Cbd - Salman Al-Farisi; Ahmad Maula Hadi; Lena Ishelmiany Ziaharah (UIN Jurai Siwo Lampung, 2026)
This study examines child protection in fasakh cases due to apostasy based on the Decision of the Cibadak Religious Court Number 3112/Pdt.G/2024/PA.Cbd, focusing on the tension between the application of the ultra petita principle and the best interests of the child principle in resolving such cases. This research employs a normative juridical method with a descriptive-analytical nature through literature review and judicial decision analysis, supported by interviews with judges. The findings reveal that the fasakh decision fulfilled both formal and substantive legal requirements, as evidenced by the proven element of apostasy as grounds for fasakh and the granting of the marriage validation (itsbat nikah) petition. However, the ruling did not explicitly regulate child custody (hadanah) or child support obligations because the judges were bound by the ultra petita principle. This condition reflects a normative-procedural gap regarding judges’ authority to provide child protection measures ex officio, potentially overlooking the best interests of the child due to the absence of legal certainty concerning post-fasakh custody, maintenance, and education. From the perspective of maqāṣid al-sharī‘ah, this situation relates to the protection of hifz al-nafs and hifz al-nasl as objectives of Islamic law in ensuring the welfare, continuity, and upbringing of children. The novelty of this study lies in its analysis of the relationship between the limitation of judicial authority under the ultra petita principle and the need for child protection in fasakh cases due to apostasy. The findings indicate the need for regulatory reinforcement granting judges ex officio authority to determine hadanah in fasakh cases in order to better safeguard the best interests of the child in judicial practice